Enhancing English reading comprehension through narrative engagement among Thai elementary students: An explanatory mixed method study - Heny Ristianty; Khairun Nissa (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
In an increasingly globalized world, English reading comprehension is an essential skill, particularly for young learners in non-native English-speaking contexts such as Thailand. This study explores the effectiveness of narrative engagement in enhancing English reading comprehension among Thai elementary students through an explanatory sequential mixed-methods design. The research involved 27 fifth and sixth-grade students from a primary school in Satun Province, Thailand. Data were collected through a reading comprehension post-test, a questionnaire, and classroom observation. Quantitative results revealed a high average post-test score (M = 86.67, SD = 8.77), indicating substantial improvement in reading comprehension following the narrative-based intervention. The findings show that students experienced emotional connection, attention, and identification with the stories. The majority of students reported feeling engaged, visualizing the scenes vividly, and relating to the characters’ experiences. These findings confirm that narrative engagement significantly contributes to students’ cognitive and emotional involvement in reading, leading to improved comprehension. The study recommends the integration of narrative texts into English language instruction to foster deeper reading experiences and motivation among young EFL learners.